Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1002/pssb.2221830223
|View full text |Cite
|
Sign up to set email alerts
|

Effective‐field renormalization‐group approach for quenched site‐dilute ising models

Abstract: The quenched site-dilute Ising model in two and three dimensions is studied by employing the effective-field renormalization-group method. The concentration dependence of the critical temperature and values of the critical concentration are obtained and compared to other different methods. Quite good results for a honeycomb lattice are achieved even by considering the smallest possible clusters. In particular, it is shown that the present formalism is able to distinguish between lattices of the same coordinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…We have found that for p = 1 (pure system) kBTJJ = 2.9557 and the critical concentration p c at which T, reduces to zero is given by pc = 0.4517. This value for p c represents an improvement to the two-spin cluster approximation without nearest-neighbour correlations of pc = 0.4294 [3,4] and is somewhat closer to the best value ofp, = 0.590 obtained by the series expansion method [5]. The value of E,(P) decreases from the value E, = 0.3591 at p = 1 to the critical value E, = 0.1791 at p = p c (see Fig.…”
Section: Role Of Nearest-neighbour Correlations In the Site-diluted Ssupporting
confidence: 76%
“…We have found that for p = 1 (pure system) kBTJJ = 2.9557 and the critical concentration p c at which T, reduces to zero is given by pc = 0.4517. This value for p c represents an improvement to the two-spin cluster approximation without nearest-neighbour correlations of pc = 0.4294 [3,4] and is somewhat closer to the best value ofp, = 0.590 obtained by the series expansion method [5]. The value of E,(P) decreases from the value E, = 0.3591 at p = 1 to the critical value E, = 0.1791 at p = p c (see Fig.…”
Section: Role Of Nearest-neighbour Correlations In the Site-diluted Ssupporting
confidence: 76%
“…Below a critical occupancy fraction this model does not experience a phase transition; p c Ϸ0.27 to 0.31. 20 If no spinodal decomposition is carried out, our model corresponds to the dilute Ising model with an occupancy fraction of 50%, well above p c , and it will have a phase transition. For larger pore sizes ͑increasing periods of spinodal decomposition͒ the connectivity of the spin-spin interactions is increased and thus we expect the phase transition to persist.…”
Section: Nature Of Demixing Phase Transition In a Porous Mediummentioning
confidence: 99%
“…The other would be based on invariance of scale, where the Eqs. (30) and (32) are equivalents, i.e.,…”
Section: F Mfrg-12 Approachmentioning
confidence: 99%
“…These two methods have been applied to a variety of magnetic spin models in obtaining of the critical properties of classical XY and Heisenberg models [30], critical behavior of two-and three-dimensional ferromagnetic and antiferromagnetic spin-ice systems [31], quenched site-dilute ising models [32] and to obtain the reduced critical temperature and exponents ν for bi-and threedimensional lattices [33].…”
Section: Introductionmentioning
confidence: 99%